2021
DOI: 10.1007/s11412-021-09340-y
|View full text |Cite
|
Sign up to set email alerts
|

Promoting regulation of equal participation in online collaboration by combining a group awareness tool and adaptive prompts. But does it even matter?

Abstract: Unequal participation poses a challenge to collaborative learning because it reduces opportunities for fruitful collaboration among learners and affects learners’ satisfaction. Social group awareness tools can display information on the distribution of participation and thus encourage groups to regulate the distribution of participation. However, some groups might require additional explicit support to leverage the information from such a tool. Therefore, this study investigated the effect of combining a group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 103 publications
2
53
1
4
Order By: Relevance
“…Within GA literature, the concept itself is mostly ill-defined since tools rather than the psychological construct itself have been the focus of most of this research. If definitions are proposed, they refer to the concept as "knowledge" (e.g., Kirsch Pinheiro & Souveyet, 2018;Strauß & Rummel, 2021;Yilmaz & Yilmaz, 2020) or "knowledge and perception" (e.g., Buder & Bodemer, 2008;Erkens & Bodemer, 2019), "understanding" (e.g., Ma et al, 2020, following Dourish & Bellotti, 1992, "information" (e.g., Kirsch Pinheiro & Souveyet, 2018;Ma et al, 2020) or "information that allows to understand" (e.g., Papadopoulos et al, 2018), "(state of) being informed" (e.g., Buder et al, 2021;Cheng et al, 2021;Lin et al, 2016;Schnaubert & Bodemer, 2019following Bodemer & Dehler, 2011, "consciousness and information" (e.g., Li et al, 2021following Gross et al, 2005 or "information that is mentally present" (Bodemer et al, 2018). Thus, to describe or even define GA, researchers often use a variety of terms related to awareness, but not quite capturing all facets.…”
Section: Defining Aspects Of Group Awarenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Within GA literature, the concept itself is mostly ill-defined since tools rather than the psychological construct itself have been the focus of most of this research. If definitions are proposed, they refer to the concept as "knowledge" (e.g., Kirsch Pinheiro & Souveyet, 2018;Strauß & Rummel, 2021;Yilmaz & Yilmaz, 2020) or "knowledge and perception" (e.g., Buder & Bodemer, 2008;Erkens & Bodemer, 2019), "understanding" (e.g., Ma et al, 2020, following Dourish & Bellotti, 1992, "information" (e.g., Kirsch Pinheiro & Souveyet, 2018;Ma et al, 2020) or "information that allows to understand" (e.g., Papadopoulos et al, 2018), "(state of) being informed" (e.g., Buder et al, 2021;Cheng et al, 2021;Lin et al, 2016;Schnaubert & Bodemer, 2019following Bodemer & Dehler, 2011, "consciousness and information" (e.g., Li et al, 2021following Gross et al, 2005 or "information that is mentally present" (Bodemer et al, 2018). Thus, to describe or even define GA, researchers often use a variety of terms related to awareness, but not quite capturing all facets.…”
Section: Defining Aspects Of Group Awarenessmentioning
confidence: 99%
“…Thus, the act of monitoring social conditions in order to initiate and adapt interaction processes may be viewed as part of a regulatory cycle guiding collaborative learning and interaction processes. This may not only include monitoring socio-cognitive conditions to focus on resolving conflicts or controversies (e.g., Gijlers & de Jong, 2009) or guiding communication based on content-related prior knowledge (e.g., Erkens & Bodemer, 2019;Nückles et al, 2005) or understanding , but may also include coordinating activities based on behavioral awareness (e.g., Janssen et al, 2011;Strauß & Rummel, 2021) or regulating emotions and socio-emotional conflict (e.g., Eligio et al, 2012;Järvenoja et al, 2020;Näykki et al, 2014). Some of these cited examples deploy static awareness tools not intended to catch the dynamics of collaboration (Engelmann et al, 2009) and thus not suitable to support the full cycle of regulatory processes (e.g., by adapting or "fine-tuning" activities; see Buder, 2011).…”
Section: The Role Of Group Awareness For Regulating Social Interactio...mentioning
confidence: 99%
“…In practice, equality of participation has often been operationalized with indices of statistical dispersion derived from either the number of task acts or the amount of talking time initiated by each group member (Bachour et al 2010;Cohen and Roper 1972). In computer-supported collaborative learning environments, the length of the messages has also been used as a unit of analysis (Kapur et al 2008;Strauß and Rummel 2021). Results from synchronous online collaboration studies (Kapur et al 2008) suggest that equality of participation is a significant positive predictor of collaborative learning outcomes and that the level for this in a group 1 3 is quite stable.…”
Section: Monitoring Together In Collaborative Learningmentioning
confidence: 99%
“…On one hand, when researchers examined the relationship between monitoring and regulation, they found that metacognitive monitoring, when used by learners, stimulates joint knowledge construction (Malmberg et al, 2017). On the other hand, if externalized monitoring between group members is ignored, it leaves less space for interaction that benefits collaboration and regulation (Strauß & Rummel, 2021). However, according to models of SRL, metacognitive monitoring allows learners to change the ways they regulate their learning to be consistent with their learning goals (Hadwin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%